PERAN KOMUNIKASI SOSIAL MASYARAKAT DALAM MENGIMPLEMENTASIKAN PROTOKOL KESEHATAN COVID-19 DI KAMPUNG PEPAYUNGEN ANGKUP - Ab, Subhan; Harahap, Viana Safrida; Putri, Susi Yunita (Telangke:Jurnal Telangke Ilmu Komunikasi, 2022)
This study aims to determine the role of Community Social Communication in Implementing the Covid-19 Health Protocol in Pepayungen Angkup Village, Silih Nara District, Central Aceh Regency and explain the Obstacles and Constraints of the Role of Community Social Communication in Implementing the Covid-19 Health Protocol in Pepayungen Angkup Village, Silih Nara District, District Central Aceh The data collection methods used in this study were interviews, literature study and observation. The data obtained were analyzed qualitatively. The results of the research on the role of Social Communication use linear communication models, circular communication models, and spiral communication models. So that the community's response to the role of social communication is in the form of direct feedback when two-way or face-to-face communication takes place, and indirect feedback. Barriers and Constraints on the Role of Community Social Communication in Implementing the Covid-19 Health Protocol in Pepayungen Angkup Village, Silih Nara District, Central Aceh Regency, namely: a). Barriers and opportunities for social communication that occur in the communication process include, social status, psychological, socio-cultural, prejudice, semantic barriers and environmental conditions. a). Providing information, cultivating feelings, and changing attitudes. This is a form of influence from social communication that is conveyed to the community when socializing. The conclusion, that social communication has played a role as social communication carried out by the Pepayungen Angkup community, Silih Nara district, Central Aceh district.